A complete evaluation method for the experimental data of flow boiling in smooth tubes. (December 2017) - Celen, Ali; Dalkılıç, Ahmet Selim
Abstract: A complete solution for boiling phenomena in smooth tubes has been giving as a procedure regarding with the calculation of convective heat transfer coefficient and pressure drop using accurate experimental data validated by flow regime maps and sight glasses on the experimental facility. The experimental study is conducted in order to investigate the effect of operating parameters on flow boiling convective heat transfer coefficient and pressure drop of R134a. The smooth tube having 8.62 mm inner diameter and 1100 mm length is used in the experiments. The effect of mass flux, saturation temperature and heat flux is researched in the range of 290–381 kg/m 2  s, 15–22 °C and 10–15 kW/m 2, respectively. The experiments revealed that the heat transfer coefficient and pressure drop are significantly affected by mass flux for all tested conditions. Moreover, the experimental results are compared with well-known heat transfer coefficient and frictional pressure drop correlations given in the literature. In addition, 122 number of heat transfer and pressure drop raw experimental data is given for researchers to validate their theoretical models.